Student and School Factor’s Influencing the Mathematics Achievement: An HLM Analysis of Indonesian Data in TIMSS 2015 - Mulia Sari Dewi (‎‎‎TAZKIYA Journal of Psychology, 2022)
Indonesia continues to participate in Trends in International Mathematics and Science Studies (TIMSS) to increase understanding of academic performance in mathematics and science. This study aims to examine the determinants of the mathematics achievement of fourth-grade students in Indonesia from student-level variables and school-level variables. Two-level hierarchical linear modeling was used to analyze data of 4025 students from 230 schools in Indonesia who had participated in the TIMSS 2015 study. The result indicated schools resource shortage has a negative direct effect on mathematics performance, while literacy and numeracy skill when the student enters the school has a positive direct effect. In student level, home resources, parents' education, self-efficacy and students' interest in mathematics have a positive direct effect. The model also revealed a cross-level interaction between school level and student level. It is the economic background of student in one school that had a moderating effect on home resource toward mathematics performance. Variance explained from students and school levels were 17% and 44%, whereas total variance explained were 28%. The results were sizeable to make some recommendation for policy consideration which social economic background and affective characteristics of students are the main determinants of mathematics performance among Indonesian Students.